Sonic the hedgehog (2018), volume 2 ebook The fate of dr. eggman. - Flynn, Ian (Sonic the Hedgehog (2018), 2020)
Following their last battle, Dr. Eggman's been mysteriously absent from Sonic's life. What shocking secret will Sonic discover when he learns the bad doctor's whereabouts? Plus, Sonic isn't the only one looking for Eggman—so's his old rival Shadow the Hedgehog! There are twists and turns in the course of this high-speed, action-packed mystery-adventure! But with a little help from his friends—including a new ally—Sonic's fast enough to overcome any obstacle! Collects issues #5-8 of the ongoing series.